The conservatory treatment of chronic cervicitis - Morales, Julio (2015)
Chronic cervicitis is common finding in gynecological patients and in those with infertility problems. The treatments generally used -electrocoagulación, electrocautery, surgery - alter the anatomical and functional conditions of the neck. This is of value especially in women with fertility problems, given the important role that plays in the cervical segment espermomigración and childbirth. This justifies the search and the use of more conservative procedures. This objective can be achieved by using antibiotics. Biological conditions of the vaginal environment are of great importance in the evolution of infection and cervical reparición process. So it is sought to keep the vaginal environment acid, by using showers and vaginal tablets. In some cases you can use estrogen administration in suitable doses. Some figures related to the material studied and the method employed is recorded in detail are given. The results have been highly satisfactory.